THE SYNERGY BETWEEN DIPLOMACY AND INTERNATIONAL RELATIONS THEORIES - Ergasheva Feruzabonu Odiljonovna (TADQIQOTLAR.UZ, 2025)
The intricate dance of global politics is shaped by a dynamic interplay between diplomacy and the theories of international relations. Diplomacy, the art of negotiation and communication between states, serves as a practical application of various theoretical frameworks that seek to explain and predict international behavior. Understanding this synergy is essential for both scholars and practitioners in the field.